Performance of WHO mid-upper arm circumference cut-off to diagnose severe acute malnutrition in under-fives - Neldy, Fahreza Aditya; Yuliarti, Klara; Andriastuti, Murti (Indonesian Pediatric Society, 2024)
Background Many studies indicate that the current WHO recommendation of cut-off value mid-upper arm circumference (MUAC) is not sensitive to detect severe acute malnutrition (SAM) in under-fives cases. Various new cut-off values have been proposed with better diagnostic values but have a wide interval, 12.1 cm—14.5 cm, which may be due to different races or habitus. Objective To evaluate the diagnostic value of MUAC in diagnosing SAM compared to the weight for height Z score (WFZ) index, to evaluate sensitivity, specificity, positive and negative predictive value of MUAC with 11.5 cm as standard cut-off, and to find an alternative cut-off value that may offer better diagnostic performance. Methods We collected 421 subjects consecutively in January-February 2020 in Cipto Mangunkusumo Hospital and Puskesmas Cengkareng. We performed brief conversations for demographic data and did the measurement of physical examination and anthropometric measurement by trained researchers and research assistants. Results Mid-upper arm circumference has excellent diagnostic value to assess SAM in under-fives with area under curve 0,939 (CI95% 0,903-0,974). Diagnostic values MUAC using cut off 11.5 cm were 21% sensitivity (Se) 21%, 99.7% spesificity (Sp)and Youden Index (YI) of 0.20. By using 13.3 cm as a new cut-off value, MUAC has Se 89%, Sp 87%, and YI of 0.76. Conclusion We conclude that WHO MUAC cut-off using 11.5 cm has lower performance to detect SAM cases than the proposed new cut-off value of 13.3 cm. New MUAC cut-off should be considered to detect more SAM cases among under-fives.